Harlem : a poem - Myers, Walter Dean, 1937- (New York : Scholastic Press, 1997)
A poem celebrating the people, sights, and sounds of Harlem.
Caldecott Medal/Honor
Notable/Best Books (A.L.A.)
School Library Journal
4.5
3-6
Keywords: Harlem (New York, N.Y.) -- Juvenile poetry; Afro-Americans -- Juvenile poetry; Children's poetry, American; Harlem (New York, N.Y.) -- Poetry; Afro-Americans -- Poetry; American poetry; Harlem (New York, N.Y.) -- Poetry; African Americans -- Poetry; American poetry